Market Trend dan Fast Food “Tantangan Sekolah dan Orang Tua” (Studi Kasus Taman Kanak-kanak Al-Falah Kerinci) - Oberini, Vinnia; Sya`roni, Sya`roni; Jamil, Zawaqi Afdal (UNIB Press, 2025)
The problem in this study is that there are still many children of Al-Falah Kindergarten in Kerinci who consume Fast food both purchased at school and provisions brought from home. This study aims to analyze the role of schools in dealing with market trends and children's tendency to consume fast food at Al-Falah Kindergarten Kerinci. The method used is qualitative descriptive, with data collection through observation, interviews, and documentation. Data is obtained from incidents, responses, and related documents. The research subjects consist of principals, teachers, and students. Data analysis uses flow model analysis techniques, which include data reduction, data presentation, and conclusion drawn. The validity of the data was checked through several steps, such as extension of participation in the field, extension of observation, and the application of triangulation. Triangulation is carried out by examining information from various sources and methods to ensure the validity of the findings. The results of the study show that schools have played an active role in educating children about the importance of a healthy diet. The programs implemented, such as balanced nutrition campaigns, cooking activities involving children, and counseling to parents about the dangers of fast food, are concrete steps in supporting healthy eating habits. However, even though these efforts have gone well, there are obstacles that affect their effectiveness. One of the main obstacles is the dependence of parents on fast food due to time constraints and work pressure. These barriers reduce the long-term impact of the programs implemented by schools. Therefore, further collaboration is needed between schools and parents to create an environment that supports healthy eating habits at home